Etika Desain dalam Media Sosial: Workshop Interaktif bagi Forum Anak Kabupaten Tangerang - Pratama, Anugrah; Mutmainnah Mutmainnah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This community service program addresses the growing ethical challenges of design practices in social media, particularly among children and adolescents. Social media platforms are not merely communication tools but persuasive digital products that influence behavior, emotions, and information consumption. This program aimed to enhance ethical design literacy among members of the Children’s forum in Tangerang Regency through an interactive workshop combining theoretical education, case studies, and practical design exercises. The methodology involved participatory training sessions, including lectures on design ethics, identification of dark patterns, privacy-by-design practices, and hands-on content creation using social media platforms. The results indicate increased participant awareness of ethical principles such as transparency, visual honesty, respect for copyright, and privacy protection. Participants demonstrated improved ability to identify unethical design elements and to produce simple yet responsible visual content. The program contributes to strengthening digital ethics awareness among young social media users and highlights the importance of collaborative, community-based approaches in fostering responsible digital culture.